AB0743 DISEASE CHARACTERISTICS OF PSORIATIC ARTHRITIS PATIENTS MAY DIFFER ACCORDING TO AGE AT PSORIASIS ONSET: CROSS-SECTIONAL ANALYSIS OF PSORIATIC ARTHRITIS-INTERNATIONAL DATABASE. (2nd June 2020) - Bilgin, E.; Bayindir, Ö.; Kasapoğlu, E.; Bakirci, S.; Solmaz, D.; Kimyon, G.; Doğru, A.; Dalkiliç, E.; Özişler, C.; Can, M.; Akar, S.; Tarhan, E. F.; et al.
Abstract : Background: Psoriasis and psoriatic arthritis (PsA) are heterogenous diseases with various disease manifestations and phenotypes. Psoriasis has a bimodal age of onset being early (before the age of 40, type 1) and late. The impact of this classification on the PsA features is not well understood. Objectives: To compare the PsA characteristics of patients with early- and late-onset psoriasis in a large, multicenter database Methods: PSART-ID (Psoriatic Arthritis-International Database) is a prospective, multicenter web-based registry (www.trials-network.org ) of patients with PsA. A detailed data collection was performed including demographics (sex, age, duration of education, smoking status, BMI), skin features (psoriasis onset date, type, initially involved site of skin, nail involvement (ever) and family history) and PsA characteristics (type of articular involvement and presence of axial, dactylitis (ever), enthesitis (ever), family history) and indices for disease activity and function (DAPSA, Leeds enthesitis index, BASDAI, BASFI, patient and physician global assessment, pain, HAQ-DI). We grouped according to the age at psoriasis onset (early onset, psoriasis before the age of 40 (EOPsO); late-onset, psoriasis after the age of 40 (LOPsO)), patient and disease characteristics of the groups were compared (1). Due to the differences among groups, following adjustments weer made: BMI for age, nail involvement for PsO disease duration, axial PsA for PsA disease duration. Results: A total of 1634 (62.8% females; EOPsO, 1108 (67.8%); LOPsO, 526 (32.2%)) patients with PsA was recruited. Rate of over-weight patients was higher in LOPsO group (66.8% vs. 86.8%, p<0.001; adjusted for age - aOR 1.55 (1.11-2.20; % 95 CI)). The EOPsO group had the scalp involvement as the initial site of skin disease more often than the LOPsO group (56.7% vs. 43.0%, p<0.001), whereas extremity involvement was more frequent as the initial finding in the LOPsO group (EOPsO vs. LOPsO 63.8% vs. 74.2%, p<0.001). Nail involvement (ever) was more prominent in EOPsO group, however, the significance was disappeared when adjusted for psoriasis duration. Interaction between gender and both axial disease and psoriatic disease family history were found (axial disease in man; EOPsO vs LOPsO; 38.0% vs. 25.4%; p=0.005; adjusted for PsA duration - aOR 0.56 (0.38-0.84; %95 CI) // psoriatic disease family history in females; EOPsO vs LOPsO; 39.5% vs. 30.1%; p=0.003; OR 0.65 (0.50-0.86; %95 CI)). Duration between PsO and PsA was significantly longer in EOPsO group (148 vs. 24 months, p<0.001). In EOPsO group, more patients had PsO preceeding PsA than LOPsO group (81.8% vs. 60.6%, p<0.001), however, synchronous disease -defined as the diagnosis of PsO and PsA within the same year- was more common in LOPsO group (16.6% vs. 30.3%, p<0.001) (Table 1). Psoriatic disease activity parameters, patient and physician reported outcomes and HAQ-DI scores were similar in both groups. Conclusion: Clinical features of PsA may be affected by the age at the onset of psoriasis. As the genetic background is different in early and late-onset psoriasis, this may suggest a different pathogenetic mechanism based on the psoriasis phenotype, also affecting the PsA features. Further prospective studies are needed to define whether the classification of PsA requires including psoriasis phenotypes as well. References: [1]Henseler T, Christophers E. Psoriasis of early and late onset: characterization of two types of psoriasis vulgaris. J Am Acad Dermatol. 1985;13(3):450-6. Disclosure of Interests: Emre Bilgin: None declared, Özün Bayindir: None declared, esen kasapoğlu: None declared, Sibel Bakirci: None declared, Dilek Solmaz: None declared, Gezmiş Kimyon: None declared, Atalay Doğru: None declared, Ediz Dalkiliç: None declared, Cem Özişler: None declared, Meryem Can: None declared, Servet Akar: None declared, Emine Figen Tarhan: None declared, Şule Yavuz: None declared, Levent Kiliç: None declared, Orhan Küçükşahin: None declared, Ahmet Omma: None declared, Emel Gönüllü: None declared, Fatih Yildiz: None declared, Duygu Ersözlü: None declared, abdurrahman tufan: None declared, Muhammet Çinar: None declared, Abdulsamet Erden: None declared, Sema Yilmaz: None declared, Seval Pehlevan: None declared, Tuncay Duruöz: None declared, Sibel Aydin: None declared, Umut Kalyoncu Consultant of: Abbvie, Amgen, Janssen, Lilly, Novartis, UCB